Gregory of Nyssa Online - Gregorius Nyssenus (Brill, 2019)
Gregory of Nyssa Online gives you access to both the Gregorii Nysseni Opera Online and the Lexicon Gregorianum Online. Together, these two resources provide the ultimate online critical text edition of Gregory of Nyssa's works based on all available known manuscripts. Gregory of Nyssa Online is introduced with a complete discussion of the textual transmission and accompanied by indices, extensive annotations on biblical, classical and patristic sources, and the most comprehensive Greek–German dictionary ever produced of the language used by Gregory of Nyssa (the Lexicon Gregorianum). Each online resource is also available as individual product